1991
DOI: 10.1111/j.1464-410x.1991.tb15318.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐endocrine Cells—A New Prognostic Parameter in Prostate Cancer

Abstract: Neuro-endocrine cells are a recognised component of prostatic ducts and acini. Half of all clinically manifest cancers show neuro-endocrine differentiation. Occult carcinomas have a lower incidence of such differentiation. Neuro-endocrine cells are of major prognostic importance and appear more reliable in predicting patients' survival than do conventional histological grading systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
2
5

Year Published

1994
1994
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(82 citation statements)
references
References 7 publications
3
72
2
5
Order By: Relevance
“…Neuroendocrine cells were found in 55% of the carcinoma specimens in this current study which is a similar incidence to that reported by other groups (Cohen et al, 1990). They express prostate-specific antigen (PSA) (Aprikian et al, 1993;Cohen et al, 1992) and are believed to represent a third epithelial type originating from a common stem cell.…”
Section: Immunocytochemical Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Neuroendocrine cells were found in 55% of the carcinoma specimens in this current study which is a similar incidence to that reported by other groups (Cohen et al, 1990). They express prostate-specific antigen (PSA) (Aprikian et al, 1993;Cohen et al, 1992) and are believed to represent a third epithelial type originating from a common stem cell.…”
Section: Immunocytochemical Analysissupporting
confidence: 90%
“…Neuroendocrine cells, which are known to secrete a variety of peptides and biogenic amines (Di Sant'Agnese, 1992), have been found in 50% of prostate cancers (Di Sant'Agnese and de Mesey Jensen, 1987) and their presence indicates a poor prognosis in this malignancy (Cohen et al, 1991). In view of these findings, immunohistochemical assays were undertaken on consecutive sections of the prostatic tissue to determine the neuroendocrine cell distribution and to establish the coexpression of VEGF and chromogranin A in this particular cell type.…”
mentioning
confidence: 99%
“…In contrast to benign epithelium, most reports on prostatic cancer tissue demonstrate heterogeneity in immunostaining of PAP and PSA and an apparent correlation between variation in stainability and tumour grade (Epstein & Eggleston, 1984;Sesterhenn et al, 1985;Feiner & Gonzales, 1986), which was also observed in our study. Like Sesterhenn et al (1985) and Feiner and Gonzales (1986) Mesy Jensen, 1987;Ro et al, 1987;Cohen et al, 1991), and it has been suggested that the demonstration of neuroendocrine features is an indicator of poor prognosis. Unlike di Sant'Agnese andde Mesy Jensen (1987) andCohen et al (1991), who used a series of different neuroendocrine markers, we applied only one monoclonal antibody raised against NSE, which may explain the lower scoring rate in our series (18%).…”
Section: Statisticsmentioning
confidence: 99%
“…Like Sesterhenn et al (1985) and Feiner and Gonzales (1986) Mesy Jensen, 1987;Ro et al, 1987;Cohen et al, 1991), and it has been suggested that the demonstration of neuroendocrine features is an indicator of poor prognosis. Unlike di Sant'Agnese andde Mesy Jensen (1987) andCohen et al (1991), who used a series of different neuroendocrine markers, we applied only one monoclonal antibody raised against NSE, which may explain the lower scoring rate in our series (18%). Furthermore, neuroendocrine differentiation is mostly focal (Cohen et al, 1991) and small tissue specimens such as core biopsies may be inadequate in demonstrating such features.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation